Increasing Teacher Competency using the contextual inquiry Learning Model through In-House Training at SD Negeri 1 Giripurwo Kapanewon Girimulyo Kulon Progo Regency Academic Year 2022/2023 - Yunarti Farida, Endang (Universitas Islam Indonesia, 2024)
This research aims to determine teachers' activities and abilities in implementing the Contextual Inquiry Learning, as well as researchers' abilities in managing IHT. School Action Research was carried out at SD Negeri 1 Giripurwo Kapanewon Girimuyo Kulon Progo Regency for the 2022-2023 Academic Year in three cycles consisting of 2 meetings in each cycle, the procedures in this research include planning, implementation/action, observation and reflection . The subjects of this research were 8 people consisting of 6 class teachers and 2 subject teachers. Qualitative data was collected in the form of active observations and the application of the